Study on improving the properties of steel slag to apply for pavement foundations - Ha, Mai Hong; Hang, Nguyen Thi Thuy (Journal of Transportation Science and Technology, 2022)
Nowadays, in Vietnam as in the world, traditional building materials are increasingly scarce while industrial waste is produced more and more. In this paper, the author uses steel slag, a byproduct of steelmaking processes, for replacing crushed aggregate in base or subbase course. Steel slag-stone dust aggregate (70% steel slag and 30% stone dust) are treated with a cement content of 4%-8%. Compressive strength (Rn), splitting tensile strength (Rech), and elastic modulus (E) at 7, 14, 28, and 56 days age are investigated. The compressive specimens and splitting tensile strength were obtained by performing tests on 152.4 mm x 116.4 mm (diameter x height). The elastic modulus was as follows 101.6mm x 116.4 mm (diameter x height). The results show that cement-treated steel slag-stone dust aggregate achieved higher compressive strength, splitting tensile strength, and modulus than the cement-treated steel slag aggregate and cement-treated steel slag-fine sand aggregate. In addition, this research proves that cement-treated steel slag-stone dust aggregate with a cement content of 4%-8% can use for base course layers.